Instructional Approaches in Science Education Across Eastern Tabuk District: Issues and Innovations - Apolinar, Hazel Aileen; Sabado, Adriano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the instructional approaches used in teaching Science in the public secondary schools across Eastern Tabuk District during School Year 2025-2026. It examined the profile of Science teacher-respondents, the extent of realization of the general objectives of Science instruction, the effectiveness of teaching parameters, the hindrances encountered by teachers, and the enrichment activities used to address these concerns. The study used a descriptive-survey design with 19 Science teachers as respondents. Data were gathered through a validated questionnaire and unstructured interviews, and were analyzed using frequency counts, percentages, and weighted mean. Findings revealed that most respondents were young, female, married, Teacher I or Teacher II, and Science majors. The general objectives of Science instruction were realized, with an average weighted mean of 4.08. Teaching parameters were rated effective for school heads (3.87), teachers (4.16), students (3.72), parents (4.16), and stakeholders (4.06). Hindrances were slightly serious, with a grand weighted mean of 2.50; student-related concerns were the most serious, particularly absenteeism, unwise use of leisure time, lack of self-confidence, and inability to express ideas. Enrichment activities were often used, with an average weighted mean of 4.15. The study concludes that Science instruction in Eastern Tabuk District is effective, yet learner-centered intervention, stronger instructional supervision, parental engagement, and continuous teacher development remain necessary to improve Science learning outcomes.
Keywords: Eastern Tabuk District; Enrichment Activities; Instructional Approaches; Science Education; Science Instruction